CORRELATION BETWEEN TRANSVERSUS ABDOMINIS MUSCLE ENDURANCE AND LIMITS OF STABILITY IN ASYMPTOMATIC HEALTHY YOUNG WOMEN (International Journal of Physiotherapy, 2018)
Background: All tasks require postural control. The appropriateness and adequacy of postural tone in the trunk muscles referred to as “Core muscles” is the key element for the control of normal postural stability in an erect position. From among the core muscles (local and global), Transversus Abdominis muscle is controlled independently of the other trunk muscles and its activation is associated with postural demand. The study aims to assess the TrA muscle endurance and Limits of Stability (Maximum Excursion-MXE and Directional Control-DC) and to determine the correlation between the two parameters.Methods: A Correlation study was performed on 100 asymptomatic healthy nulliparous urban women of 18-25 years’ age with Body Mass Index of 18.5- 27.9 kg/m². Participants performed two tests in random order; Prone Test for TrA muscle endurance using Pressure Biofeedback Unit and LOS Test using the NeuroCom Balance Manager®. The outcome measures were TrA endurance (Number of 10 seconds hold) and MXE (%) and DC (%) of the LOS test.Results: Mean (mean ± SD) values were TrA endurance: 4.93 ± 3.31, Maximum Excursion (%): 92.8 ± 7.69 and Directional Control (%): 84.53 ± 3.17. Results showed a significant positive correlation between TrA endurance and MXE whereas no significant correlation was observed between TrA endurance and DC (Pearson’s correlation test; r=0.201 and r= -0.084, respectively at p